Antidiabetic and Cardioprotective Effects of Pharmacological Inhibition of GRK2 in db/db Mice - Cipolletta, Ersilia (Int J Mol Sci, 2019)
Despite the availability of several therapies for the management of blood glucose in diabetic patients, most of the treatments do not show benefits on diabetic cardiomyopathy, while others even favor the progression of the disease. New pharmacological targets are needed that might help the management of diabetes and its cardiovascular complications at the same time. GRK2 appears a promising target, given its established role in insulin resistance and in systolic heart failure. Using a custom peptide inhibitor of GRK2, we assessed in vitro in L6 myoblasts the effects of GRK2 inhibition on glucose extraction and insulin signaling. Afterwards, we treated diabetic male mice (db/db) for 2 weeks. Glucose tolerance (IGTT) and insulin sensitivity (ITT) were ameliorated, as was skeletal muscle glucose uptake and insulin signaling. In the heart, at the same time, the GRK2 inhibitor ameliorated inflammatory and cytokine responses, reduced oxidative stress, and corrected patterns of fetal gene expression, typical of diabetic cardiomyopathy. GRK2 inhibition represents a promising therapeutic target for diabetes and its cardiovascular complications.